A psychoanalytical interpretation of the characters in A.C. Jordan’s novel Ingqumbo yeminyanya - L.L. Kwatsha (Literator, 2007)
Psychoanalysis is a way of treating certain nervous disorders of the mind by examining all the ways that sufferers can be helped to remember their past life, dreams, et cetera. This is an effort to find hidden forgotten anxieties or desires influencing one’s behaviour without one’s knowledge thereof. The aim of this article is to make a detailed interpretation of the characters Zwelinzima and Thembeka/Nobantu in A.C. Jordan’s novel, “Ingqumbo yeminyanya”, so as “to uncover the hidden causes of the neurosis in order to relieve the character of his or her conflicts, thus dissolving the distressing symptoms” (Gräbe, 1986). This article will look at the behaviour of the different characters in Jordan’s novel. Psychoanalysis is rooted in the idea that humans have unconscious longings that must be analysed in order to understand behaviour. The accent of the article will fall on how psychoanalysis can help the reader, critic or analyst to penetrate the inner workings of the minds of the characters.